High‐frequency oscillations detected in ECoG recordings correlate with cavernous malformation and seizure‐free outcome in a child with focal epilepsy: A case report. Issue 2 (22nd May 2017) - Liu, Su; Quach, Michael M.; Curry, Daniel J.; Ummat, Monika; Seto, Elaine; Ince, Nuri F.
Summary: Epilepsy associated with cavernous malformation (CM) often requires surgical resection of seizure focus to achieve seizure‐free outcome. High‐frequency oscillations (HFOs) in intracranial electroencephalogram (EEG) are reported as potential biomarkers of epileptogenic regions, but to our knowledge there are no data on the existence of HFOs in CM‐caused epilepsy. Here we report our experience of the identification of the seizure focus in a 3‐year‐old pediatric patient with intractable epilepsy associated with CM. The electrocorticographic recordings were obtained from a 64‐contact grid over 2 days in the epilepsy monitoring unit (EMU). The spatial distribution of HFOs and epileptic spikes were estimated from recording segments right after the electrode placement, during sleep and awake states separately. The HFO distribution showed consistency with the perilesional region; the location of spikes varied over days and did not correlate with the lesion. The HFO spatial distribution was more compact in sleep state and pinpointed the contacts sitting on the CM border. Following the resection of the CM and the hemosiderin ring, the patient became seizure‐free. This is the first report describing HFOs in a pediatric patient with intractable epilepsy associated with CM and shows their potential in identifying the seizure focus.